The Gender Equality in Research Scale: A tool for monitoring and encouraging progress on gender integration in research for and in development - Paez Valencia, Ana Maria; Ihalainen, Markus; Elias, Marlène; Sijapati Basnett, Bimbika (CGIAR Research Program on Forests, Trees and Agroforestry, 2019)
This brief discusses a monitoring and learning tool – the Gender Equality in Research Scale (GEIRS) – designed to assess the level of gender integration across a CRP’s research portfolio and at different stages of the research and development cycle.